PENGARUH KEBIJAKAN DIVIDEN TERHADAP VOLATILITAS HARGA SAHAM DENGAN INFLASI SEBAGAI VARIABEL MODERASI - Patricia Maurin Aten; Dade Nurdiniah (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to analyze the effect of dividend payout ratio and dividend yield on stock price volatility with inflation as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017. Documentary data (secondary) from financial statements and annual reports are used in this study. The population of this study includes manufacturing companies listed on the Stock Exchange from 2013-2017 and IPOs at least from 2013. The sampling method used in this study was purposive sampling, of which 44 companies were included in the criteria of this study. The analytical method carried out in this study is multiple regression. The results show that the variable that has a significant influence on stock price volatility is only the dividend payout ratio. The more dynamic the dividend payout ratio, the higher the stock price volatility, and vice versa. Research also shows the results that the inflation variable does not moderate the effect of dividend payout ratio and dividend yield on stock price volatility. Keywords: dividend payout ratio, dividend yield, stock price volatility, inflation